Synthesis of C60 Nanotube from Pyrolysis of Plastic Waste (Polypropylene) with Catalyst - Amal Abbood et al. (مجلة بغداد للعلوم)
Fullerene nanotube was synthesized in this research by pyrolysis of plastic waste Polypropylene (PP) at 1000 ° C for two hours in a closed reactor made from stainless steel using molybdenum oxide (MoO3) as a catalyst and nitrogen gas. The resultant carbon was purified and characterized by energy dispersive X-ray spectroscopy (EDX), X-ray powder diffraction (XRD). The surface characteristics of C60 nanotubes were observed with the Field emission scanning electron microscopy (FESEM). The carbon is evenly spread and has the highest concentration from SEM-EDX characterization. The result of XRD and FESEM shows that C60 nanotubes are present in Nano figures, synthesized at 1000 ° C and with pyrolysis temperature 400° C. The synthesis operation doing in one reactor and limited time.